Mystification as astray in forests: Workplace tobacco promotion rivalry among Muslims - Abdul Manan, Kamaruzzaman; Ahmad, Che Mahzan; Mohd Samin, Ahmad Shalihin (Pusat Pembangunan Penyelidikan (PPP) Kolej Universiti Islam Antarabangsa Selangor (KUIS, 2017)
This article highlights the findings on Muslim smokers’ responses to the legislation of workplace tobacco-free policy as well as their attitude towards smoking. The data were collected in July 2015. A total of 200 smokers were selected as research respondents. The research conducted a survey whereby respondents’ smoking patterns, attitudes towards smoking, attitudes and barriers towards quitting and perception towards existing tobacco-free policy implementation were studied. The results show that there are contradictions between smokers’ positive perception of workplace tobacco-free policy and their desire to remain smokers. The findings indicate that there is cognitive dissonance among the smokers. The confusion that occurs is likened to mystification as astray in forests. Thus, there is a need to transform the initial strategies in executing tobacco cessation activities. The article suggests a new dimension of cessation activities whereby tobacco cessation needs to change from a promotional perspective into a competitive outlook. Perhaps it is worth looking back at Michael Porter’s “The Competitive Forces That Shape Strategy”. This business model analyses competition within a particular industry as well as a business strategy development. The tobacco industry is known to be among the most advanced marketers in the world, thus smoking cessation needs a relook on the tactics that are used by their competitors in order for them to improve the effectiveness of cessation programmes. As Sun Tzu used to say, “He who knows them will be victorious; he who knows them not will fail”.